2012
DOI: 10.3382/ps.2011-01907
|View full text |Cite
|
Sign up to set email alerts
|

A wire-flooring model for inducing lameness in broilers: Evaluation of probiotics as a prophylactic treatment

Abstract: Bacterial chondronecrosis with osteomyelitis (BCO) is the most common cause of lameness in commercial broilers. Bacteria entering the blood via translocation from the respiratory system or gastrointestinal tract spread hematogenously to the proximal epiphyseal-physeal cartilage of rapidly growing femora and tibiae, causing BCO. We tested the hypothesis that rearing broilers on wire flooring should increase the incidence of BCO by persistently imposing additional torque and shear stress on susceptible leg joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
109
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 68 publications
3
109
0
Order By: Relevance
“…Human studies of increased IP have been associated with enteric infections, inflammatory bowel disease, obesity, type-1 diabetes, liver diseases, irritable bowel syndrome and celiac disease (Skouroliakou et al, 2016). Limited in vivo research has shown that increased IP can lead to increased bacterial translocation , coccidiosis (Chapman, 2014) and lameness (Wideman et al, 2012) in chickens. These diseases can impact health and welfare leading to reduced efficiency and economic loss (Zuidhof et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human studies of increased IP have been associated with enteric infections, inflammatory bowel disease, obesity, type-1 diabetes, liver diseases, irritable bowel syndrome and celiac disease (Skouroliakou et al, 2016). Limited in vivo research has shown that increased IP can lead to increased bacterial translocation , coccidiosis (Chapman, 2014) and lameness (Wideman et al, 2012) in chickens. These diseases can impact health and welfare leading to reduced efficiency and economic loss (Zuidhof et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Dextran sodium sulphate (DSS) ingestion, fasting (Kuttappan et al, 2015;Vicuna et al, 2015b), dexamethasone (Vicuna et al, 2015a) and wire floor stress (Wideman et al, 2012) have recently been employed as models of increased IP in chickens. These studies have been conducted in one strain of chickens (Cobb).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial proliferation and the ensuing immunological response generate the necrotic abscesses and voids that are pathognomonic for BCO [1–5]. BCO has been diagnosed in broilers in Australia, Canada, Europe and the US, and is considered the most common cause of lameness in broilers [2,4,6–10]. Multiple opportunistic organisms in mixed cultures have been isolated from BCO lesions, including predominately Staphylococcus spp ., Escherichia coli , and Enterococcus spp .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, there are indications that some probiotic strains may have a protective effect on the translocation of opportunistic pathogens. Indeed, in a recent study using a wire flooring model for inducing lameness in broilers, Wideman et al (2012) showed that a commercial blend of probiotic microorganisms significantly reduced the numbers of lame birds.…”
Section: Probioticsmentioning
confidence: 99%